Dialysis Adequacy and Risk of Dementia in Elderly Hemodialysis Patients - Kim, Hyung Woo; Jhee, Jong Hyun; Joo, Young Su; Yang, Ki Hwa; Jung, Jin Ju; Shin, Ji Hyeon; Han, Seung Hyeok; Yoo, Tae-Hyun; Kang, Shin-Wook; Park, Jung Tak (Frontiers in Medicine, 2021)
Objective: Dementia is prevalent among elderly patients undergoing hemodialysis. However, the association between dialysis adequacy and the risk of dementia is uncertain. Methods: A total of 10,567 patients aged >65 years undergoing maintenance hemodialysis who participated in a national hemodialysis quality assessment program were analyzed. The patients were classified into quartile groups based on single-pool Kt/V levels. The associations between single-pool Kt/V and the development of dementia, Alzheimer’s disease (AD), and vascular dementia (VD) were examined. Results: The mean age of the patients was 72.9 years, and 43.4% were female. The mean baseline single-pool Kt/V level was 1.6 ± 0.3. During a median follow-up of 45.6 (45.6–69.9) months, there were 27.6, 23.9, and 2.8 events/1000 person-years of overall dementia, AD, and VD, respectively. The incidences of overall dementia, AD, and VD were lowest in the highest single-pool Kt/V quartile group. Compared with the lowest single-pool Kt/V quartile, the risks of incident overall dementia and AD were significantly lower in the highest quartile (sub-distribution hazard ratio [sHR]: 0.69, 95% confidence interval [CI]: 0.58–0.82 for overall dementia; sHR: 0.69, 95% CI: 0.57–0.84 for AD). Inverse relationships were found between the risks of developing overall dementia and AD, and single-pool Kt/V. However, no significant relationship was observed between single-pool Kt/V levels and VD development. Conclusions: Increased dialysis clearance was associated with a lower risk of developing dementia in elderly hemodialysis patients.